Pengaruh Pijat Abdomen dengan Fennel Oil terhadap Kejadian Kolik Bayi 0-6 Bulan di Desa Karangpring - Ayu Ratna Eka Kartika Candra Kirana; Widia Shofa Ilmiah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Infant colic is a condition in which infants cry excessively and continuously without a clear cause, often following a specific pattern, such as occurring at certain times or at night. The purpose of this study was to determine the effect of abdominal massage with fennel oil on the incidence of colic in infants in Karangpring Village. This study employed an observational approach with data collection through observation sheets. Data analysis was conducted using the Wilcoxon Signed Ranks test due to the non-normal distribution of the data. Most infants exhibited a history of colic with high crying frequency. After two sessions of abdominal massage using fennel oil per week, there was a significant reduction in colic symptoms (p < 0.001). Anise oil, as an essential oil, is believed to have antispasmodic properties, alleviate gastrointestinal symptoms, and enhance absorption through stimulation of the nervous and hormonal systems. There is an effect of abdominal massage with fennel oil on reducing the incidence of colic in infants aged 0–6 months. It is hoped that midwives can continue to provide education and motivation to parents and caregivers to perform abdominal massage as an additional method to reduce the duration of colic in infants.